The Impact of Hallux Valgus on Function and Quality of Life in Females. Issue 1 (January 2022) - Gordon, David; Lewis, Thomas L.; Ray, Robbie
Category: Bunion Introduction/Purpose: The effect of hallux valgus (HV) on health-related quality of life (HRQOL) and the relationship between radiographic severity of deformity and patient reported outcome measures (PROMs) is poorly understood. The aim of this study was to compare the HRQOL of female patients with HV to the UK population. The secondary aim was to assess the correlation between PROMs, including HRQOL, with radiographic severity of deformity. Methods: Weight bearing radiographic data (hallux valgus (HVA) angle; intermetatarsal (IM) angle) were measured in consecutive female patients presenting with symptomatic HV. Each patient prospectively completed the Euroqol EQ-5D-5L questionnaire (EQ- 5D), Visual Analogue Scale for Pain (VAS-Pain) and Manchester Oxford Foot Questionnaire (MOXFQ). Data were stratified into age ranges and compared with an EQ-5D United Kingdom general population reference dataset. Pearson R correlation values were calculated for the PROMs and radiographic deformity. Results: Between July 2015 and March 2020, 425 consecutive female patients presented with symptomatic HV for consideration for surgery. EQ-5D-5L data were prospectively collected for 396 of these patients (93.2%). EQ-5D-5L Index scores were significantly worse for females with HV when compared with females in the general population. There was a moderate correlation with MOXFQ Index score and EQ-5D-5L Index (R=-0.51, p<0.001) and VAS-Pain scores (R=0.54, p<0.001). There was no correlation between radiographic HV deformity and HRQOL measures or MOXFQ scores. Conclusion: Female patients presenting with HV deformity have a significantly reduced quality of life compared with the UK general population. The radiographic severity of deformity did not correlate with health-related quality of life measures or foot and ankle specific PROMs. Foot and ankle specific clinical PROMs do correlate with HRQOL and may be a better marker of the negative effect of symptomatic hallux valgus deformity on quality of life.